Double Threshold Based Load Balancing Approach by Using VM Migration for the Cloud Computing Environment (International Journal of Engineering and Computer Science, 2015)
Cloud computing is emerging as a new paradigm for next generation computing in the field of computer science and informationtechnology because of their attractive services such as adaptive, online, value added and pay as use scheme. Virtualization is the coretechnology in the cloud computing, which allow the sharing of physical resources. With the help of virtualization single physical device canbe share by the multiple users. So it increased the resource utilization. Cloud is a very large in size and having complex structure. Cloudresources are heterogeneous and geographically distributed and the resource demanded by the user may change dynamically on runtime. Sothe resource management and the resource scheduling in such a large-scale distributed environment is a very challenging task. In cloudenvironment each data center can contain number of host, so there may be a situation when some hosts are overloaded and some areunderloaded. To avoid this situation we proposed a double threshold based load balancing approach, where threshold is decided based onthe utilization. This approach motivated by the fact that overloaded situation can’t be avoided, but can be control by assigning the dynamicthreshold. For assigning the dynamic threshold we monitored host utilization for each 20 Second and assign the threshold based on theutilization in the previous interval. Experiment result shows that our approaches reduce the energy consumption and minimize the numberof migration